Search behavior for health services for the detection of tuberculosis - Jéssica Oliveira Tomberg; Lílian de Moura Lima Spagnolo; Jenifer Harter; Martina Dias da Rosa Martins; Roxana Isabel Cardozo Gonzales (Universidade Federal de Santa Maria, 2020)
Objective: to investigate the detection of pulmonary tuberculosis from the search behavior for health services in towns located in Rio Grande do Sul. Methods: cross-sectional and descriptive study conducted between 2013 and 2014, through interviews with 290 people with pulmonary tuberculosis in towns of the south region of the country. When analyzing data, we used descriptive statistics, designing search behavior flows in search of the diagnosis of the disease. Results: specialized services were used by 39.7% (115) of people for the first visit, offering sputum smear microscopy to 64.1% (186), chest X-ray to 57.2% (166) and testing for the human immunodeficiency virus to 62.7% (182). We found that 37.5% (109) were diagnosed in the first health service sought and 62.4% (181) sought other services. Conclusion: the detection of pulmonary tuberculosis takes place, primarily, in specialized services, followed by the Emergency Care Units and the Primary Health Care Units.